Determinants of intention to change health-related behavior and actual change in patients with TIA or minor ischemic stroke. Issue 4 (April 2016) - Brouwer-Goossensen, Dorien; Genugten, Lenneke van; Lingsma, Hester; Dippel, Diederik; Koudstaal, Peter; Hertog, Heleen den
Abstract: Objective: To assess determinants of intention to change health-related behavior and actual change in patients with TIA or ischemic stroke. Methods: In this prospective cohort study, 100 patients with TIA or minor ischemic stroke completed questionnaires on behavioral intention and sociocognitive factors including perception of severity, susceptibility, fear, response-efficacy and self-efficacy at baseline. Questionnaires on physical activity, diet and smoking were completed at baseline and at 3 months. Associations between sociocognitive factors and behavioral intention and actual change were studied with multivariable linear and logistic regression. Results: Self-efficacy, response efficacy, and fear were independently associated with behavioral intention, with self-efficacy as the strongest determinant of intention to increase physical activity (aBeta 0.40; 95% CI 0.12–0.71), adapt a healthy diet (aBeta 0.49; 95% CI 0.23–0.75), and quit smoking (aBeta 0.51; 95% CI 0.13–0.88). Intention to change tended to be associated with actual health-related behavior change. Conclusion: Self-efficacy, fear, and response-efficacy were determinants of intention to change health-related behavior after TIA or ischemic stroke. Practice implications: These determinants of intention to change health-related behavior after TIA or ischemic stroke should be taken into account in the development of future interventions promoting health-related behavior change in these group of patients.